HUBUNGAN PERSONAL HYGIENE DENGAN RESIKO KECACINGAN PADA SISWA SEKOLAH DASAR NEGERI - Samuel Marganda Manalu; Citrayuni Saragih (Jurnal Penelitian Kesmasy, 2020)
Worm disease is a contagious disease and is a type of disease that is mostly experienced by children in Indonesia, which accounts for 80%. Personal hygiene, especially at the age of elementary school children, is very important, considering that at this age intestinal worm infections transmitted through the soil are very high. The aims of this study to determine the relationship of personal hygiene with the risk of helminthiasis in Elementry School. This research using quantitative with the type of research that is observational survey. The population in this study were all students of Elementry School and the sample of 77 peoples, the total sampling technique and method of collecting data by interviewing indirectly using a questionnaire sheet. The analysis of data is using chi-square then obtained a value of p = 0.037 <α = 0.05 there was a relationship between personal hygiene and the risk of worms. For this reason, it is hoped that the school will provide knowledge about personal hygiene such as every bath must use soap, wash hands with soap after defecation, wear footwear when playing outdoors, cut children's nails once a week, use clean drinking water, drink well-cooked water, not defecating in any place, providing latrines and clean water for school children to prevent worm infections.